Pushing Higgs effective theory to its limits - Brehmer, Johann; Freitas, Ayres; López-Val, David; Plehn, Tilman (Physical review, 2016)
At the LHC, an effective theory of the Higgs sector allows us to analyze kinematic distributions in addition to inclusive rates, although there is no clear hierarchy of scales. We systematically analyze how well dimension-6 operators describe LHC observables in comparison to the full theory, and in a range where the LHC will be sensitive. The key question is how the breakdown of the dimension-6 description affects Higgs measurements during the upcoming LHC run for weakly interacting models. We cover modified Higgs sectors with a singlet and doublet extension, new top partners, and a vector triplet. First, weakly interacting models only generate small relevant subsets of dimension-6 operators. Second, the dimension-6 description tends to be justified at the LHC. Scanning over model parameters, significant discrepancies can nevertheless arise; their main source is the matching procedure in the absence of a well-defined hierarchy of scales. While these issues require vigilance, they should not present a major problem for future LHC analyses.